2017
DOI: 10.1182/bloodadvances.2017006064
|View full text |Cite
|
Sign up to set email alerts
|

Two distinct CXCR4 antagonists mobilize progenitor cells in mice by different mechanisms

Abstract: Pharmacological mobilization of hematopoietic progenitor cells (HPCs) is used clinically to harvest HPCs for bone marrow transplants. It is now widely accepted that the CXCR4:CXCL12 chemokine axis plays a critical role in the retention of HPCs in the bone marrow, and CXCR4 antagonists have been developed for their mobilization. The first of this class of drugs to be US Food and Drug Administration-approved was the bicyclam AMD3100. In addition to mobilizing HPCs and leukocytes in naïve mice, AMD3100 has been s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 58 publications
2
24
0
Order By: Relevance
“…Our studies revealed that chalcone 4-phosphate, when administered alone, had no effect on circulating numbers of murine neutrophils; however, it significantly suppressed the mobilisation of neutrophils by AMD3100. 23 This is consistent with a model whereby the AMD3100-induced rise in circulating CXCL12 is critical for neutrophil mobilisation (Figure 3). In contrast, KRH3955, a distinct CXCR4 antagonist, does not reverse the CXCL12 gradient across the BME, but still efficiently mobilises neutrophils from the bone marrow, implying that KRH3955 disrupting the CXR4/CXCL12 retention axis directly is sufficient for mobilisation under homeostasis ( Figure 3).…”
Section: Mechanism Of Action Of Amd3100supporting
confidence: 90%
See 3 more Smart Citations
“…Our studies revealed that chalcone 4-phosphate, when administered alone, had no effect on circulating numbers of murine neutrophils; however, it significantly suppressed the mobilisation of neutrophils by AMD3100. 23 This is consistent with a model whereby the AMD3100-induced rise in circulating CXCL12 is critical for neutrophil mobilisation (Figure 3). In contrast, KRH3955, a distinct CXCR4 antagonist, does not reverse the CXCL12 gradient across the BME, but still efficiently mobilises neutrophils from the bone marrow, implying that KRH3955 disrupting the CXR4/CXCL12 retention axis directly is sufficient for mobilisation under homeostasis ( Figure 3).…”
Section: Mechanism Of Action Of Amd3100supporting
confidence: 90%
“…To test this hypothesis, we made use of chalcone 4‐phosphate, a CXCL12‐neutralising ligand. Our studies revealed that chalcone 4‐phosphate, when administered alone, had no effect on circulating numbers of murine neutrophils; however, it significantly suppressed the mobilisation of neutrophils by AMD3100 . This is consistent with a model whereby the AMD3100‐induced rise in circulating CXCL12 is critical for neutrophil mobilisation (Figure ).…”
Section: Mechanism Of Action Of Amd3100supporting
confidence: 89%
See 2 more Smart Citations
“…Previous reports showed that the CXCR4-CXCL12 interaction is a key factor in the retention of the HSPCs in the BM. Loss of CXCL12 in the BM or inhibition of the CXCR4-CXCL12 interaction using AMD3100 led to both significantly reduced retention of HSPCs in the BM and facilitated their egress to the blood (Bonig et al, 2009;Dar et al, 2011;Redpath et al, 2017;Rosenkilde et al, 2004;Winkler et al, 2012). In our model where CXCL12 is broadly overexpressed, including in the blood (Figure 1Bii), BM specific CXCR4-CXCL12 interaction is perturbed, likely leading to the increased mobilization ( Figures 5B, and S4C).…”
Section: Discussionmentioning
confidence: 75%